Increasing Student Engagement through Course Attributes, Community, and Classroom Technology: Lessons from the Pandemic - Cristine Donham; Cathy Pohan; Erik Menke; Petra Kranzfelder (Journal of Microbiology & Biology Education, 2022)
ABSTRACT While many STEM (science, technology, engineering, and mathematics) instructors returned to in-person instruction in fall 2021, others found themselves continuing to teach via online, hybrid, or hybrid flexible (i.e., hyflex) formats. Regardless of one’s instructional modality, the findings from our own and other studies provided insight into effective strategies for increasing student engagement and decreasing cognitive overload. As part of this perspective, we included data from undergraduate students, many of whom are first generation and low income and from marginalized backgrounds, to identify instructional practices that helped them thrive and succeed during the recent COVID-19 pandemic. More specifically, we explored the various pedagogies and technologies utilized during emergency remote teaching to identify best practices as we considered the future of teaching. In sharing best practices at our institution, we aimed to provide a framework for deep reflection among the readers and the identification of practices to start, stop, and/or continue at their own institutions.